Under-use of migrants' employment skills linked to poorer mental health - Reid, Alison (2012)
Objective: Since the mid-1990s Australia's immigration program has focused on encouraging skilled migration. This study investigated skill usage in three longitudinal studies of immigrants to Australia and examined if there is an association with mental health status. Methods: Three Longitudinal Surveys of Immigrants to Australia (LSIA), with multiple data collection waves, were conducted between 1994 and 2006. Some 5,192 primary applicants participated in LSIA1, 3,124 in LSIA2 and 9,865 in LSIA3. Data collected included demographics and employment history in all surveys as well as mental health in LSIA1 and 2. Results: Among migrants in LSIA 1, 49% reported working in jobs in which they used their skills sometimes, rarely or never, 31/2 years after immigrating. This was not solely explained by English language proficiency as 47% of migrants who reported speaking English well or very well did not use their qualifications in their job. Migrants who did not use their job qualifications at wave three had a worse GHQ-12 score at wave three after adjusting for age, sex, country of birth and highest educational qualification. There was no difference in wave one or wave two GHQ-12 score between those who did or did not use their job qualifications at wave three. The pattern was similar for those migrants in LSIA 2. Conclusions and Implications: There is a large under-utilisation of employment skills in the migrant population in Australia up to 31/2 years after immigrating. This is associated with poorer mental health. © 2012 Public Health Association of Australia.